Angiotensin-Converting Enzyme Gene D/I Polymorphism in Relation to Endothelial Function and Endothelial-Released Factors in Chinese Women - Lv, Yuanyuan; Zhao, Wenying; Yu, Laikang; Yu, Ji-Guo; Zhao, Li (Frontiers in Physiology, 2020)
Many studies have investigated the relationship between angiotensin converting enzyme (ACE) D/I polymorphism and cardiovascular disease or endothelial dysfunction; however, hardly any of these studies has taken aging or menopause into consideration. Furthermore, despite many studies have examined the effects of endothelial-released factors (ERFs) on endothelial function, no study has evaluated the differences of ERFs on endothelial function related to ACE D/I polymorphism and menopause status. To answer these questions, 391 healthy Chinese women over a wide range of ages (22-75 years) were enrolled and divided into pre-menopause group (Pre-MG) and post-menopause group (Post-MG). ACE D/I genotype was examined and the women were then classified into either DI/II or DD genotype. Brachial endothelium flow-mediated dilatation (FMD) and plasma levels of ERFs: nitric oxide (NO), endothelin-1 (ET-1), and angiotensin II (Ang II) were measured. The results showed that frequencies of ACE D/I genotypes were in accordance with the Hardy-Weinberg equilibrium, and frequency of I allele was higher than D allele. In Pre-MG, FMD was significantly higher in women of DI/II than DD (P = 0.032), and age-dependent in both genotypes (DD, P = 0.0472; DI/II, P < 0.0001). In Post-MG, FMD was similar between women of DI/II and DD, and age-dependent only in women of DI/II (P < 0.0001). In Pre-MG, Ang II level was significantly higher in women of DD than DI/II (P = 0.029), and FMD was significantly correlated with all ERFs in women of DD (NO, P = 0.032; ET-1, P = 0.017; Ang II, P = 0.002), but only with Ang II in women of DI/II (P = 0.026). In Post-MG, no significant difference was observed in any ERF between women of DI/II and DD, and FMD was only significantly correlated with ET-1 in women of DD (P = 0.010). In summary, women of DI/II were superior in FMD to DD in pre-menopause, and more age-dependent than DD in post-menopause, which was closely associated with ERFs. In conclusion, Chinese pre-menopausal women of DI/II seem to have lower risk in developing cardiovascular disease than DD, and the risk seems similar in post-menopausal women of the two genotypes.